2018
DOI: 10.1002/pon.4841
|View full text |Cite
|
Sign up to set email alerts
|

Oregon's Familias en Acción replicates benefits for underserved cancer co‐survivors through Un Abrazo Para la Familia

Abstract: Our replication study provides a useful roadmap for others focusing on the psychosocial needs of Hispanic/Latino cosurviving family members of cancer. A manualized 12-hour training program based on the initial discovery and efficacy work was developed to train promotoras as a part of this study. The manual provides a clear protocol for others to replicate our intervention and evaluation procedures. Abrazo may be particularly important for family-centered care if the family does not have the cancer knowledge or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Previous studies of Abrazo demonstrated significant improvements in cancer knowledge and selfefficacy among cosurvivors in Tucson Marshall, 2014) and in Oregon (Marshall et al, 2018), as well as among the survivors associated with these cohorts (Marshall et al, 2020). Information alleviates distress and is a prerequisite for full participation in shared decisionmaking Mesters et al, 2001;Sutherland et al, 2008).…”
Section: Public Significance Statementmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies of Abrazo demonstrated significant improvements in cancer knowledge and selfefficacy among cosurvivors in Tucson Marshall, 2014) and in Oregon (Marshall et al, 2018), as well as among the survivors associated with these cohorts (Marshall et al, 2020). Information alleviates distress and is a prerequisite for full participation in shared decisionmaking Mesters et al, 2001;Sutherland et al, 2008).…”
Section: Public Significance Statementmentioning
confidence: 98%
“…The long-range goal was to expand access to Abrazo for underserved cancer survivors, and cosurvivors. Implementation scope, as part of an initiative to reduce disparities for underserved U.S. populations, through the Merck Foundation Alliance to Advance Patient-Centered Cancer Care, has been reported elsewhere (Marshall et al, 2018; 2020). Research questions for the implementation included the following:…”
Section: Purpose Of the Present Studymentioning
confidence: 99%
“…Fidelity may also refer to how CHWs communicate with the community, which acts as a form of assessment for how CHWs achieved the training objectives. In total, seven studies mentioned fidelity (Ford et al, 2014;Marshall et al, 2018;Matthew et al, 2020;Mojica et al, 2021;Moore-Monroy et al, 2013;Nebeker & Lopez-Arenas, 2016;Serrano et al, 2018).…”
Section: Gaps In Training Program Evaluation Reportingmentioning
confidence: 99%
“…I received a NIH NCI-sponsored Ruth L. Kirschstein National Research Service Award (NRSA) for Individual Senior Fellowship during 2007-2009. The NRSA allowed me to obtain the data needed to develop a psychoeducational, skill-building, and tailored intervention designed to increase the quality of life, including well-being and productivity, of low-income female family members who were providing socioemotional and/or financial support to a cancer survivor relative who had either cervical or breast cancer-this intervention became Abrazo [2,[9][10][11][12]. By first researching the needs of local low-income families facing cancer, irrespective of stage, Abrazo was then developed to meet the specific needs of these family members who had reported that they (1) needed more information about cancer, (2) had trouble communicating with their provider, and (3) needed information regarding resources available to them [1].…”
Section: Communication Skills As Mentioned Earlier Speaking Inmentioning
confidence: 99%
“…Abrazo was developed with cultural context and other social determinates of health factors in mind [8]. Abrazo is a psychoeducational evidence-based intervention that has demonstrated significant outcomes in cancer knowledge and self-efficacy [2,[9][10][11] for low-income caregiving co-survivors of cancer, as well as for survivors or care recipients [12].…”
Section: Introductionmentioning
confidence: 99%